Coping Stress of Javanese Health Workers during the Covid-19 Pandemic - Agustina, Navi; Martaningrum, Alit; Haryati, Siti; Ananthayuda, Erlangga; Giri, Roiz Santria; Prihartanti, Nanik (Prosiding University Research Colloquium, 2022)
The Covid-19 virus that entered Indonesia in early March 2020 made many changes in all joints of life. The field that gets a lot of hope, spotlight, including a lot of ridicule, even stigma is health workers. This study uses a qualitative method, by interviewing 5 Javanese health workers, in November 2021. The results of the research produce 3 themes, namely 1 Causes of stress for health workers are a. a drastic increase in the number of patients b. PPE that makes mobility difficult c. increased workload d. patient behavior e conflict with coworkers f. lack of health facilities 2. Coping Stress of health workers is carried out by: a. patient and calm b. implementation of religious values such as patience and sincerity, c. application of Javanese family values such as: ngalah, nrimo ing pandum, rila, d. refreshing e. share stories, and f. time management. 3. Factors that affect coping, the presence of a. family education values and b. family and social support.